Regulation of hepatic lipogenesis by the zinc finger protein Zbtb20 - Gan Liu (Nature Portfolio, 2017)
De novo lipogenesis is tightly controlled by hormonal and nutritional signals and plays an important role in energy homoeostasis. Here, Liu et al. show that zinc finger protein ZBTB20 regulates the expression of key glycolytic and lipogenic genes by modulating ChREBP expression and transcriptional activity.